2001
DOI: 10.1007/s007750100238
|View full text |Cite
|
Sign up to set email alerts
|

The trail of chromium(III) in vivo from the blood to the urine: the roles of transferrin and chromodulin

Abstract: The chromium-binding oligopeptide chromodulin (also known as low-molecular-weight chromium-binding substance) has been shown to activate the tyrosine kinase activity of the insulin receptor in response to insulin and has been proposed to be part of a novel autoamplification mechanism for insulin signaling. The model requires that Cr3+ be moved from the blood to insulin-sensitive tissues in response to insulin and subsequently be lost in the urine as chromodulin; however, the model has not been tested by in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 30 publications
7
43
0
3
Order By: Relevance
“…Ujemny bilans Cr obserwowano u pacjentów cierpiących na cukrzycę typu I (54). Zwiększoną sekrecję tego pierwiastka z moczem stwierdzono także u szczurów po domię-śniowym podaniu insuliny (22,61).…”
Section: Toksykokinetykaunclassified
“…Ujemny bilans Cr obserwowano u pacjentów cierpiących na cukrzycę typu I (54). Zwiększoną sekrecję tego pierwiastka z moczem stwierdzono także u szczurów po domię-śniowym podaniu insuliny (22,61).…”
Section: Toksykokinetykaunclassified
“…Metal ions may bind to specific serum proteins to form metal-protein complexes (Torti and Torti 1994, Borguet et al 1995, Sun et al 1999, BarOr et al 2001, Clodfelder et al 2001, Qian et al 2002, Eitinger et al 2005. Such metal-protein complexes produced from degradation of metal alloys are immunologically active in vitro (Hallab et al 2001).…”
Section: Metal-induced Immune Responsesmentioning
confidence: 99%
“…It has been shown that physiological insulin indirectly promotes Cr mobilization to insulin-sensitive tissues, possibly in association with the effect of insulin on glucose transport [17][18][19][20] . In agreement with these findings, the present study shows that insulin injection promotes Cr accumulation in fat, liver, and muscle.…”
Section: Discussionmentioning
confidence: 99%